Cooperative Entrepreneurial Decisions: Do Educational, Environment, and Family Aspects Matters? - Sujianto, Agus Eko; Astutiningsih, Sri Eka; Asiyah, Binti Nur; Aswad, Muhammad; Estiningrum, Sri Dwi; Narmaditya, Bagus Shandy (International Journal of Psychosocial Rehabilitation, 2020)
The objectives of this study are: (1) analyzing aspects of education in influencing cooperative entrepreneurial decisions, (2) analyzing environmental aspects in influencing cooperative entrepreneurial decisions, and (3) analyzing family aspects in influencing cooperative entrepreneurial decisions. The research was conducted at Madrasah Aliyah Negeri (MAN) in Tulungagung Regency with a sample of all members of the student cooperative that was about 133 respondents. The data were collected using questionnaires. With multiple regression analysis, the findings indicate that (1) the aspect of education influences cooperative entrepreneurial decisions positively insignificantly; (2) the environmental aspect influences the cooperative entrepreneurial decision negatively insignificantly, and (3) the family aspect influences the cooperative entrepreneurial decision negatively insignificantly.